THE JURISPRUDENTIAL ROLE IN RESOLVING CUSTOMARY INHERITANCE DISPUTES - Poespasari, Dr. Ellyne Dwi; Erlangga, Afga Samudera (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2025)
Customary inheritance law is influenced by three kinship systems: patrilineal, matrilineal, and parental. Disputes over customary inheritance often arise in traditional communities due to dissatisfaction with the division of assets. While these conflicts are commonly resolved through family deliberation or traditional institutions, dissatisfaction with a chief's decision can escalate to legal action in court. This research aims to understand how customary inheritance disputes are resolved within these kinship systems and how Supreme Court jurisprudence is applied following these resolutions. This study uses a legal methodology with a multi-faceted approach. A statute approach is used to analyze relevant laws and existing legal precedents. A conceptual approach examines applicable legal theories and doctrines, while a case approach is employed to analyze specific, legally binding court decisions that illustrate the development of customary inheritance law. The findings reveal that while initial resolutions are sought through customary channels, a persistent dissatisfaction can lead to legal action. However, the effective application of judicial precedent is hindered by a lack of knowledge within customary legal communities. Nevertheless, these court decisions have brought about significant change, particularly in Batak communities, where several legal precedents have led to women being granted and receiving inheritance rights.